AN INDUSTRIAL VISIT TO PT ATLANTIC BIRURAYA AS A LEARNING MANAGEMENT STRATEGY TO SUPPORT WORK READINESS - Rubingatun Rubingatun; Bagus eka Febriansyah; Imtihana aulia Ramadhoni; Kiki Melinda Rosalia; Rully Erika Firanda; Sisilia Anggraini (Universitas Dharmawangsa Medan, 2026)
Industrial visits can be positioned as part of experiential learning managed within a learning management framework to prepare students for entering the workforce. The main issue addressed in this study is the limited understanding of students regarding real industrial conditions, which has implications for their work readiness. This study aims to examine the role of industrial visits at PT Atlantic Biruraya as a learning strategy in supporting students' work readiness. This research employs a qualitative descriptive approach, with data collected through observation, limited interviews, and documentation during the implementation of the activity. The findings indicate that industrial visits, when managed through structured stages of planning, implementation, and evaluation, are able to provide more systematic learning experiences. The activity also enriches students' understanding of industrial operational systems, professional work culture, and encourages the development of work-related attitudes such as discipline and responsibility. Therefore, industrial visits can be optimally utilized as an experiential learning management strategy to support students' work readiness.